Sovereignty, just wars and the responsibility to protect - Jara Gómez, Ana María (2019)
The concept of international humanitarian intervention, or “just war”, is surrounded by a certain ambiguity because the international system is constructed on the basis of state sovereignty and despite the fact that globalization has made it difficult for governments to exercise it, borders have been strengthened. It becomes fundamental to contextualize each and every one of the interventions separately. The doctrine of the ‘Responsibility to Protect’ does not consider sovereignty of the State as an end in itself, but it does insist that military intervention is merely only one of the due international responsibilities, which imply other actions related to human rights.